7x+7(-2x-6)=-112

Simple and best practice solution for 7x+7(-2x-6)=-112 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x+7(-2x-6)=-112 equation:


Simplifying
7x + 7(-2x + -6) = -112

Reorder the terms:
7x + 7(-6 + -2x) = -112
7x + (-6 * 7 + -2x * 7) = -112
7x + (-42 + -14x) = -112

Reorder the terms:
-42 + 7x + -14x = -112

Combine like terms: 7x + -14x = -7x
-42 + -7x = -112

Solving
-42 + -7x = -112

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '42' to each side of the equation.
-42 + 42 + -7x = -112 + 42

Combine like terms: -42 + 42 = 0
0 + -7x = -112 + 42
-7x = -112 + 42

Combine like terms: -112 + 42 = -70
-7x = -70

Divide each side by '-7'.
x = 10

Simplifying
x = 10

See similar equations:

| -2(r+6)=-39 | | 2x-4=-4x | | 4m-(-2)=18 | | 9p^2=24p-16 | | 3x-5(5x+17)=69 | | 8*15/6 | | 1/7*6/7 | | 4-(-2)=18 | | 2x+5x-6=15 | | 21x-5=5(4x+2)-5 | | -4x+6(-2x-2)=84 | | 2r^2-3=-3-2(2r-r^2) | | 1/4t+1=9/4 | | 500+0.35x=2.5x | | 3x-7+x^2+3x-4=11 | | 2(2y+8)-y=16 | | 10(v+2)-2v=2(4v+3)-11 | | 7/9*21/2 | | 1/4t+1=21/4 | | 2/3*1/7 | | -8x-(4x+6)=14 | | ax+ry=n | | 4x=-27 | | -6x-4(x-12)=158 | | 3x^2+-8x+4=0 | | 3/5x=-7/8 | | x^4-28x^2+100=0 | | -3(3-2r)=6r+21 | | (1/4)(3t-7)=(t+7)/8 | | -8-8/3 | | 4x^2-7x+11x=2x+6 | | -8-16/8 |

Equations solver categories